2004
DOI: 10.1182/blood-2003-07-2456
|View full text |Cite
|
Sign up to set email alerts
|

Preventing restimulation of memory B cells in hemophilia A: a potential new strategy for the treatment of antibody-dependent immune disorders

Abstract: Memory B cells are responsible for the rapidly emerging antibody response after antigen reexposure. The signals required for the restimulation of memory B cells have not been fully explained. We used a murine model of anti-factor VIII (FVIII) antibody responses in hemophilia A to study the requirements for the restimula-tion of FVIII-specific memory B cells and their differentiation into anti-FVIII anti-body-producing cells. We were particularly interested in the significance of activated T cells and costimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
189
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(199 citation statements)
references
References 48 publications
9
189
1
Order By: Relevance
“…Our data, however, show clearly that administration of anti-ICOS mAb over an extended period effectively promotes tolerance to the transgene. This is different from the results reported in a hemophilia mouse model reported by Hausl et al, 48 suggesting that the interference with ICOS-ICOSL interaction by anti-ICOSL monoclonal antibody does not inhibit restimulation and differentiation of FVIII-specific memory B cell. This difference could be because the model used was one of an established disease and/or that the blocking antibodies anti-ICOS and anti-ICOSL act differently.…”
Section: Discussioncontrasting
confidence: 57%
“…Our data, however, show clearly that administration of anti-ICOS mAb over an extended period effectively promotes tolerance to the transgene. This is different from the results reported in a hemophilia mouse model reported by Hausl et al, 48 suggesting that the interference with ICOS-ICOSL interaction by anti-ICOSL monoclonal antibody does not inhibit restimulation and differentiation of FVIII-specific memory B cell. This difference could be because the model used was one of an established disease and/or that the blocking antibodies anti-ICOS and anti-ICOSL act differently.…”
Section: Discussioncontrasting
confidence: 57%
“…The protection has been correlated with high levels of induction of growth-inhibitory antibodies and not with effector CD4 ϩ T cells (20,21). But there is a poor understanding of the B cell responses to PfMSP-1 19 that protect against bloodstage infection in vivo in humans.…”
mentioning
confidence: 99%
“…In this study we investigated the development of memory B cells and their differentiation into antibody-secreting cells (ASCs) and the protective capacity upon PfMSP-1 19 administration. Our findings indicate that memory responses to PfMSP-1 19 both in the bone marrow (BM) and spleen were impaired, and adoptive transfer of MBCs resulted in the formation of short-lived antibody-secreting plasma cells and a short-lived antibody response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, analyses in FVIII-deficient mice have demonstrated that abrogation of T-cell help using antibodies to CD40-ligand (CD154), CD80, or CD86, or using CTLA4-Ig constructs, which impairs the cross-talk between APCs and T cells, prevented the anti-FVIII immune response as well. [89][90][91][92][93] Interestingly, some patients who completely lack the endogenous FVIII molecule, and presumably do not develop natural tolerance to FVIII, never develop FVIII inhibitors, while others do. This suggests that the emergence of FVIII inhibitors in severe hemophilia A patients is not merely due to a lack of natural tolerance to FVIII.…”
Section: Actors Of the Anti-fviii Immune Responsementioning
confidence: 99%